Algebra – yes, it is.. Commentary for Study modulus - Dosinas, Gediminas (Lietuvos matematikos rinkinys, 1998)
In this article mathematical studies modulus of the third term are examined in a general passage of mathematics course i n the KTU. The instruction of modulus for the third term mathematics studies, commentaries and problems of the faculty of information is given.